Significados Que Tienen Los y Las Jóvenes Frente al Autocuidado En el Marco del Aislamiento Por Covid-19 (2021)
This research work seeks to investigate the meanings that young people construct in relation to self-care acquired throughout their lives and put into practice in the context of the pandemic. Therefore, we inquired about the physical, mental and social care, through a semistructured interview, since this type of interviews have fixed guiding questions, but the participants are free to choose their answer, that is to say, mostly open questions, in order to adapt the answers to the guiding questions of the research, thanks to these questions focused on the learning that they have, it is possible to identify that the youth have clear physical care guidelines that the WHO provides us, where they manage to identify most of the WHO described in their appearances, In this way, by identifying these guidelines, young people were able to have a slightly more pleasant quarantine in terms of their physical health, and also that young people in their experience throughout their lives were able to acquire guidelines for the care of their mental health, Therefore, in times of quarantine they will have to be able to at least have a little lower mental health problems (stress and emotions control) and finally that they manage to understand the factor that strengthens social health, which is the good social interaction, from the acquisition of knowledge, improvement in empathy, coping with difficulties from different patterns of visitation and tranquility, empathy and peace.